2008
DOI: 10.1002/mc.20428
|View full text |Cite
|
Sign up to set email alerts
|

Fucoidan from Laminaria cichorioides inhibits AP‐1 transactivation and cell transformation in the mouse epidermal JB6 cells

Abstract: Fucoidan, a sulfated polysaccharide extracted from brown seaweeds, has anticoagulant and antithrombotic activities. Unlike heparine, fucoidan is known to exhibit anticarcinogenic activities. However, the underlying molecular mechanisms of the chemopreventive activities of fucoidan are not understood. Here we report that fucoidan from Laminaria cichorioides inhibited the epidermal growth factor (EGF) or 12-O-tetradecanoylphorbol-13-acetate (TPA)-induced neoplastic cell transformation, but had less cytotoxic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 48 publications
(57 reference statements)
3
22
0
Order By: Relevance
“…and S. japonica at different reproductive stages against normal mouse epidermal (JB6 Cl41), human breast cancer (T-47D), and melanoma (RPMI-7951) cell lines was tested (Fig. Similar results were obtained by Lee et al [32] [33], who showed that purified fucoidans isolated from Laminaria cichorioides and L. gurjanovae were nontoxic to JB6 mouse epidermal cells. The cells were incubated for 24 h with different concentrations of fucoidans (100, 200, 400, and 800 mg/ ml) isolated from vegetative (Al sp-sF and Sj-sF2) and reproductive tissues (Al sp-fF and Sj-fF2) of the brown algae.…”
supporting
confidence: 77%
“…and S. japonica at different reproductive stages against normal mouse epidermal (JB6 Cl41), human breast cancer (T-47D), and melanoma (RPMI-7951) cell lines was tested (Fig. Similar results were obtained by Lee et al [32] [33], who showed that purified fucoidans isolated from Laminaria cichorioides and L. gurjanovae were nontoxic to JB6 mouse epidermal cells. The cells were incubated for 24 h with different concentrations of fucoidans (100, 200, 400, and 800 mg/ ml) isolated from vegetative (Al sp-sF and Sj-sF2) and reproductive tissues (Al sp-fF and Sj-fF2) of the brown algae.…”
supporting
confidence: 77%
“…The amount of sulfate groups has been reported to play role for anticoagulant activity of fucoidans. There are very few reports [14][15][16][17]4] in the literature on the relationship between chemical properties and anticancer activity of different fucoidans. In our case, we did not find a correlation between amount of sulfate groups and anticancer activity, as fucoidan ShF2 does not have sulfate groups, but its anticancer activity is the same as for fucoidan ShF3 with 16.9% of sulfate.…”
Section: Cytotoxicity and Anticancer Activity Of Purified Fucoidansmentioning
confidence: 98%
“…Actually, in experiments with neoplastic transformation of JB6 mouse epidermal cells induced by EGF or 12- O -tetradecanoylphorbol-13 acetate, a Russian-Korean group of scientists reported that inhibition of EGFR phosphorylation was followed by inhibition of the activities of some extracellular signal regulated kinases that resulted in the inhibition of AP-1 nuclear factor transactivation [66,67]. …”
Section: Polysaccharides From Brown Algaementioning
confidence: 99%